Ground-Based Gamma-Ray Spectrometer Application on Drone-Borne: Suitability and Height Attenuation - Syaeful, H.; Muhammad, A. G.; Rachael, Y.; Pratiwi, F.; Rosianna, I.; Ngadenin, N; Indrastomo, F. D.; Ciputra, R. C.; Sukadana, I. G.; Adimedha, T. B.; Karunianto, A. J. (Atom Indonesia, 2024)
Rapid development in the use of unmanned aerial vehicles (UAVs) in many applications, such as topographic mapping, agricultural management, marine monitoring, and others, has also brought the radiometric mapping application to this drone-borne application. Before the application, several corrections are performed to the data, including stripping corrections obtained from calibration results and height attenuation corrections. This study aims to determine the effectiveness and the height attenuation of the ground-based spectrometer attached to the drone. The method is carried out to determine the optimal altitude and conduct direct testing in the field of a small detector of 0.1 l of RS-125 gamma-ray spectrometer using drone-borne radiometric applications. In ideal conditions without obstacles in the flying path, 15 m is considered the ideal height, proportional to the detector size. Based on the results of field measurements at a drone height of 24 m, the comparison of drone and ground data is acceptable for dose rate, thorium, and potassium concentration with Pearson correlation of 0.67, 0.49, and 0.45, respectively. The drone measurement result is less acceptable for uranium data, with a Pearson correlation of 0.05 to the ground measurement. In conclusion, the RS-125 gamma-ray spectrometer is generally suitable for drone-borne radiometric applications.